A new approach to characterize very-low-level radioactive waste produced at hadron accelerators. (April 2017) - Zaffora, Biagio; Magistris, Matteo; Chevalier, Jean-Pierre; Luccioni, Catherine; Saporta, Gilbert; Ulrici, Luisa
Abstract: Radioactive waste is produced as a consequence of preventive and corrective maintenance during the operation of high-energy particle accelerators or associated dismantling campaigns. Their radiological characterization must be performed to ensure an appropriate disposal in the disposal facilities. The radiological characterization of waste includes the establishment of the list of produced radionuclides, called "radionuclide inventory", and the estimation of their activity. The present paper describes the process adopted at CERN to characterize very-low-level radioactive waste with a focus on activated metals. The characterization method consists of measuring and estimating the activity of produced radionuclides either by experimental methods or statistical and numerical approaches. We adapted the so-called Scaling Factor (SF) and Correlation Factor (CF) techniques to the needs of hadron accelerators, and applied them to very-low-level metallic waste produced at CERN. For each type of metal we calculated the radionuclide inventory and identified the radionuclides that most contribute to hazard factors. The methodology proposed is of general validity, can be extended to other activated materials and can be used for the characterization of waste produced in particle accelerators and research centres, where the activation mechanisms are comparable to the ones occurring at CERN. Highlights: We developed a radiological characterization process for radioactive waste produced at particle accelerators. We used extensive numerical experimentations and statistical analysis to predict a complete list of radionuclides in activated metals. We used the new approach to characterize and dispose of more than 420 t of very-low-level radioactive waste.